DIPLOMATIC PROTECTION FOR CITIZEN BASED ONINTERNATIONAL LAW - Nashiruddin Surya Wijaya; Lina Hastuti (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The state has the obligation to provide diplomatic protection for its citizens. Based on the principle of maximum protection the state is obliged to provide protection for its own citizens. However, in reality the state is often unable to carry out the responsibility of providing protection, even other states actually carry out oppressionactsto their citizens. This study aims to analyze the regulation related to diplomatic protection for its citizen who is abroad based on international law, and analyze the implementation of the 2006 ILC Draft Articles on Diplomatic Protection to the case of football players. The type of this study which used was normative legal research. Diplomatic protection was carried out with three conditions, namely, an international wrongful act, Exhaustion of Local Remedies and Link of Nationality. There was significant difference related to Diplomatic Protection which carried out by developed country and developing country.